Memória e violência na dramaturgia de Guillermo Calderón - Luísa Lagoeiro Ferreira (2020)
In a context of political crisis in many South American countries, with a rise of the conservative right and a still fragile democracy, the works Neva (2006) and Escola (2013) by the Chilean Guillermo Calderón were analysed. Both dramatic texts make reference to the dictatorial period and to the violence imposed by this regime in Chile as in other Latin American countries. This choice is based on the hypothesis that with the passing of the years the work of the author went through considerable aesthetic changes according to the variations in Chilean and Latin American political contexts. Thus, our goal is to analyse how the dramaturgy of Guillermo Calderón modifies itself from the difference observed in the writing of both texts. In the face of the dramaturgy works we might ask: What is the importance of the memory of dictatorship to Latin America and what is the role of Latin American Contemporary Theatre in the revival and reflection of this traumatic memory? Through analysis of texts that draw on the past to debate about the present time we intend to learn how the continuity of this theme in dramatic literature could allow for a greater understanding of current events and how it could pose as a relief and an alert in moments of vivid political instability in Latin America.